2000
DOI: 10.1063/1.481613
|View full text |Cite|
|
Sign up to set email alerts
|

Structures, energies, vibrational spectra, and electronic properties of water monomer to decamer

Abstract: The correlation of various properties of water clusters (H2O)n=1–10 to the cluster size has been investigated using extensive ab initio calculations. Since the transition from two dimensional (2-D) (from the dimer to pentamer) to 3-D structures (for clusters larger than the hexamer) is reflected in the hexamer region, the hexamer can exist in a number of isoenergetic conformers. The wide-ranging zero-point vibrational effects of the water clusters having dangling H atoms on the conformational stability by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
159
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 311 publications
(173 citation statements)
references
References 110 publications
12
159
0
2
Order By: Relevance
“…For the same set of cyclic clusters, both the AMOEBA model and MP2/TZ2P++ optimization 98 yield average O‚‚‚O nearest neighbor distances that decrease with increasing cluster size. However, our O‚‚‚O distances are systematically longer than ab initio estimates.…”
Section: Resultsmentioning
confidence: 99%
“…For the same set of cyclic clusters, both the AMOEBA model and MP2/TZ2P++ optimization 98 yield average O‚‚‚O nearest neighbor distances that decrease with increasing cluster size. However, our O‚‚‚O distances are systematically longer than ab initio estimates.…”
Section: Resultsmentioning
confidence: 99%
“…The SW trimers are very good; the r OO matches the experimental distance, 59 while the energy and dipole are almost identical to ab initio results. 38,60 However since the ab initio r OO does not agree with the experimental value, it is not possible to determine how accurate the energy and dipole are. In case of the tetramer the SW models all have too large r OO as compared to experiment 61 and, somewhat surprising, even larger r OO than in the trimer.…”
Section: Water Trimer and Tetramermentioning
confidence: 99%
“…[10,11,13,22,23] At the same time, theoretical IR spectra of water clusters are frequently simulated based on quantum-chemical computations to help determine the molecular structure of water clusters through comparing with experimental results. [5,6,[24][25][26] Regarding quantum-chemical studies of vibrations of larger clusters, the IR spectra of different (H 2 O) 20 isomers were calculated by Fanourgakis et al at the level of MP2 theory, where they demonstrated the different spectral features for the isomers and that these features could be related to the spectra of their constituent fragments. [25] Lenz and Ojamäe studied the evolution of IR spectra with increasing cluster size for various clusters containing up to 30 molecules by B3LYP hybrid density functional theory, and the contributions to the spectrum from different types of H-bond donor and acceptor configurations were analyzed.…”
Section: Introductionmentioning
confidence: 99%